THE USE OF RECOMBINANT DNA TECHNOLOGY TO ENHANCE BETA-CAROTENE CONTENT IN CASSAVA (GOLDEN CASSAVA) - Abakar, Sonia; Ali, Fatima; Saleh, Mahamat (Techno Agriculturae Studium of Research, 2025)
Cassava (Manihot esculenta) is a staple crop widely grown in tropical regions, providing a major source of carbohydrates. However, its nutritional content is limited, particularly in essential micronutrients such as provitamin A. Beta-carotene, a precursor of vitamin A, plays a critical role in human health, particularly in preventing vitamin A deficiency, which is prevalent in many developing countries. Enhancing beta-carotene content in cassava could significantly improve its nutritional value and address public health concerns related to micronutrient malnutrition. The objective of this study is to use recombinant DNA technology to genetically engineer cassava varieties with enhanced beta-carotene content, creating what is commonly referred to as “Golden Cassava.”This research employed genetic transformation techniques, specifically Agrobacterium-mediated transformation, to introduce genes responsible for the biosynthesis of beta-carotene into cassava. Candidate genes, including those from the daffodil and maize, were selected to enhance the carotenoid biosynthesis pathway. Transgenic cassava plants were developed, and molecular analysis, including PCR and Southern blotting, was used to confirm the presence and integration of the introduced genes. Beta-carotene content in the transgenic plants was measured using high-performance liquid chromatography (HPLC). The results showed that the genetically modified cassava plants exhibited a significant increase in beta-carotene content compared to the wild-type varieties. The transgenic lines demonstrated enhanced nutritional quality without affecting other agronomic traits. In conclusion, recombinant DNA technology has proven to be an effective tool for biofortifying cassava with beta-carotene. This approach offers a promising strategy for addressing vitamin A deficiency and improving the nutritional value of cassava in regions where it is a major food source.